Legal Protection of Consumers in Buying and Selling Dropshipping In The Perspective Of Islamic Law And Laws and Regulation - Koto, Ismail (Inspiring Law Journal, 2022)
This research is a descriptive analysis with a comparative law approach. This type of research is normative juridical. The data sources of this research are revelatory data sources and secondary legal sources. The data collection tool for this research is document study. To analyze the data obtained, qualitative data analysis was used. Based on this research, it is implemented that the concept of a dropshipping trading system both in Islam and the existing laws in Indonesia is not much different, it's just that what distinguishes dropshipping in Islamic law in buying and selling makes an agreement called a contract or an agreement regarding the product that is traded. disagreements with the form of supervision of the regulatory-law which is not only supervised by the government but also supervised by parties who have worked together to oversee dropshipping trading activities